Theory And Practice Of Mediation In Gayo Indigenous Peoples : Theory And Practice Of Mediation In Gayo Indigenous Peoples - sabela (International Asia Of Law and Money Laundering (IAML), 2025)
Mediation is one of the dispute resolution mechanisms that has long been practiced in customary law communities in Indonesia, including the Gayo Indigenous people who inhabit the Central Aceh, Bener Meriah, and Gayo Lues regions. This study aims to examine the theory and practice of mediation in the Gayo customary law community and its relationship with the national legal system. The problem raised in this study is how the concept of mediation is applied in Gayo indigenous peoples and the extent to which the practice intersects with Indonesian positive law. This research uses normative juridical method with qualitative approach through literature study on the sources of law and current literature. The results showed that mediation in the Gayo customary law community was carried out by traditional institutions informally by prioritizing the value of deliberation and restorative justice. Gayo customary mediation has proven effective in resolving disputes without further conflict and in line with the spirit of non-litigation settlement in the national legal system. This finding confirms the importance of strengthening the legality of indigenous institutions within the national legal framework as a form of protection and empowerment of Indigenous Peoples.